Large-Vessel Occlusion Stroke Treated by Endovascular Thrombectomy in Patient with Coronavirus Disease 2019 - Tsurumi, Yuko; Matsubara, Noriaki; Yokoyama, Hayato; Hososhima, Osamu; Tsurumi, Arihito (Asian Journal of Neurosurgery, 2022)
We report a case of acute ischemic stroke caused by large-vessel occlusion in a patient infected with coronavirus disease 2019 (COVID-19) who was treated by endovascular thrombectomy. The patient was a 41-year-old man hospitalized with moderately severe COVID-19. Fourteen days after the onset of COVID-19, dysarthria and right hemiplegia were observed, and acute occlusion of the left middle cerebral artery was diagnosed. Mechanical thrombectomy was performed with a stent retriever while the patient was under local anesthesia and sedation. The staff involved in the intervention was as minimal as possible. The interventional surgeon wore a disposable surgical gown, an N95 mask, a face shield, and two pairs of gloves, while the patient was fitted with a surgical mask. The intervention involved the usual procedures, such as sheath insertion, catheter manipulation, and stent deployment, and the thrombus was removed with the stent retriever. The time from puncture to recanalization was within 30 minutes. No infection was observed in our staff or inpatients after the intervention. Thus, we were able to perform neuroendovascular treatment without spreading COVID-19 by taking appropriate measures to prevent infection.
Keywords: COVID-19; ischemic stroke; thrombectomy; infection prevention